A generic soil velocity model that accounts for near-surface conditions and deeper geologic structure. Issue 140 (January 2021) - Marafi, Nasser A.; Grant, Alex; Maurer, Brett W.; Rateria, Gunjan; Eberhard, Marc O.; Berman, Jeffrey W.
Abstract: Near-surface soil conditions can significantly alter the amplitude and frequency content of incoming ground motions – often with profound consequences for the built environment – and are thus important inputs to any ground-motion prediction. Previous soil-velocity models (SVM) have predicted shear-wave velocity profiles based on the time-averaged shear-wave velocity in the upper 30 m ( V S30 ). This article presents a generic soil-velocity model that accounts both for near-surface conditions ( V S30 ) and deeper geologic structure, as represented to the depth at which the profile reaches a velocity of 1.0 km/s ( Z 1.0 ). To demonstrate the advantages of our new SVM, we apply it to the Cascadia Region of North America, where numerous geologic basins and glaciated landscapes give rise to a wide range of V S30 and Z 1.0 combinations. This soil velocity model yields good estimates of site response across all site conditions, and significantly improves upon a model calibrated using only V S30 data. In conjunction with existing models that describe the deep velocity structure of the region (e.g., (Stephenson et al., 2017) [27]; the proposed model is particularly suited for use in regional-scale predictions of site response, liquefaction, landslides, infrastructure damage, and loss. The proposed methodology is broadly applicable to the development of SVMs elsewhere, and with improved understanding of near-surface and deep velocity structures, can facilitate more accurate ground-motion predictions globally. Highlights: Predicts near-surface shear-wave velocity profiles while accounting for deeper structure. Soil profile predictions are conditioned on V S30 and Z 1.0 Suited for large-scale/regional site profile and amplification estimates. Better estimates site response than existing models calibrated to other regions.